Pyrexia And Liver Injury After A Second SARS-CoV-2 Vaccination: Macrophage Activation Manifested In Liver - Tomiko Ryu; Yusuke Onozato; Ayano Umeda; Keiko Abe; Akio Mimori; Hideaki Miura; Yukiko Komeno (International Journal of Coronaviruses, 2023)
Vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-Co V-2) has contributed to control of the coronavirus disease 2019 (COVID-19). On the other side, vaccination of SARS-CoV-2 could trigger autoimmune or inflammatory diseases. We present a 50-year-old female with well-controlled optic neuromyelitis with prednisolone (PSL) maintained at a dose of 2.5 mg/day. She ran a fever and liver injury was indicated 5 weeks after a second COVID-19 vaccination (BNT162b2 mRNA/Pfizer ). Liver biopsy showed accumulation of macrophages around the central veins, identified using anti-CD68 antibodies. As the treatment, cyclosporine A improved liver injury. COVID- 19 vaccination may have triggered liver inflammation due to cytokine storm via macrophage activation in the liver.
Keywords: COVID-19 Vaccine